Comparing the efficiency of base and multiplicative selection indices for yield and quality traits in Cassava: Article Retracted by the Authors - Ntivuguruzwa, Severin; Edema, R.; Gibson, Paul; Alladassi, M.E.B.; Nduwumuremyi, A.; Abincha, W.; Kawuki, R. (Journal of Experimental Sciences, 2020)
The efficiency of two selection indices; base index and the multiplicative index was compared to determine the effectiveness of each in identifying superior genotypes in cassava (Manihot esculent Crantz) population. Genotypic data on various yield and quality traits among 570 cassava genotypes were used to construct these selection indices. The efficiency of these indices was compared by determining the performance means of each genotype for studied traits and computing selection differentials of each index. Best linear unbiased predictions (BLUPs) for dry matter content and harvest index were also used for comparison of the two selection indices. The base index produced high-performance means of all five studied traits and proved to be more efficient compared to the multiplicative index in the improvement of cassava genotypes. In addition, the base index produced high selection differentials for three out of five studied traits. It was concluded that the base index is useful in cassava germplasm selection